XRF analysis of sediment core PHE1 retrieved from the Pheneos Polje (Peloponnese, Greece) - Seguin, Joana; Avramidis, Pavlos; Haug, Annette; Kessler, Torben; Schimmelmann, Arndt; Unkel, Ingmar (In: Seguin, J et al. (2020): Geochemical and sedimentological record of sediment core PHE1 retrieved from the Pheneos Polje (Peloponnese, Greece) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.921424, 2020)
The sediment core PHE1 (37.85114° N, 22.33510° E) was retrieved from the eastern bay of the Pheneos Polje, Peloponnese Greece, in spring 2017 using a piston corer (Stitz type). The sedimentary sequence covers 390 cm (sedimentary units 1 - 9). The core was scanned at 0.5 cm resolution with an Avaatech X-ray Fluorescence (XRF) core scanner and the raw data presented here is displayed as element counts per second (cps). The core sequence covers the largest part of the Holocene and was analysed to reconstruct ecosystem and landscape changes as well as palaeoclimatic fluctuations in southern Greece.
Keywords: Eastern Mediterranean; Geochemistry; Greece; palaeoenvironment; Peloponnese; Sedimentology